Pale Karang di Tablasufa - Masyhuri Imron (LIPI Press, 1998)
Pele karang is a rule for marine resources management practiced by community in Tablasufa, Kemcatan Depapre, Jayapura. The rule is related by ownership of marine area claimed by this community. When pele karang is applied no body may exploitate marine resources in that area, within about one year. Closing and opening of pele karang is done by ondoafi Appaseray and Demane. Pele karang is useful for marine resources conservation, because not exploited in the long periode. Socially pele karang is also useful, because it can help to fulfil the needs of the members of that community.